Primary Angiitis of the CNS: A Systematic Review and Meta-analysis. Issue 6 (18th November 2021) - Beuker, Carolin; Strunk, Daniel; Rawal, Rajesh; Schmidt-Pogoda, Antje; Werring, Nils; Milles, Lennart; Ruck, Tobias; Wiendl, Heinz; Meuth, Sven; Minnerup, Heike; Minnerup, Jens
Abstract : Background and Objectives: To facilitate and improve the diagnostic and therapeutic process by systematically reviewing studies on patients with primary angiitis of the CNS (PACNS). Methods: We searched PubMed, looking at the period between 1988 and February 2020. Studies with adult patients with PACNS were included. We extracted and pooled proportions using fixed-effects models. Main outcomes were proportions of patients with certain clinical, imaging, and laboratory characteristics and neurologic outcomes. Results: We identified 46 cohort studies including a total of 911 patients (41% biopsy confirmed, 43% angiogram confirmed, and 16% without clear assignment to the diagnostic procedure). The most frequent onset symptoms were focal neurologic signs (63%), headache (51%), and cognitive impairment (41%). Biopsy- compared with angiogram-confirmed cases had higher occurrences of cognitive impairment (55% vs 39%) and seizures (36% vs 16%), whereas focal neurologic signs occurred less often (56% vs 95%). CSF abnormalities were present in 75% vs 65% and MRI abnormalities in 97% vs 98% of patients. Digital subtraction angiography was positive in 33% of biopsy confirmed, and biopsy was positive in 8% of angiogram-confirmed cases. In 2 large cohorts, mortality was 23% and 8%, and the relapse rate was 30% and 34%, during a median follow-up of 19 and 57 months, respectively. There are no randomized trials on the treatment of PACNS. The initial treatment usually includes glucocorticoids and cyclophosphamide. Discussion: PACNS is associated with disabling symptoms, frequent relapses, and significant mortality. Differences in symptoms and neuroimaging results and low overlap between biopsy and angiogram suggest that biopsy- and angiogram-confirmed cases represent different histopathologic types of PACNS. The optimal treatment is unknown.